2022
DOI: 10.3390/cancers14030693
|View full text |Cite
|
Sign up to set email alerts
|

Biopsy and Margins Optimize Outcomes after Thermal Ablation of Colorectal Liver Metastases

Abstract: Background: Thermal ablation is a definitive local treatment for selected colorectal liver metastases (CLM) that can be ablated with adequate margins. A critical limitation has been local tumor progression (LTP). Methods: This prospective, single-group, phase 2 study enrolled patients with CLM < 5 cm in maximum diameter, at a tertiary cancer center between November 2009 and February 2019. Biopsy of the ablation zone center and margin was performed immediately after ablation. Viable tumor in tissue biopsy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Although the area at or above the thermal breakpoint of 43 °C includes tissue/skin that may not present a palpable tumor, providing this treatment at areas surrounding the tumor margin could improve the treatment's efficacy to eliminate tumor cells at the margins that are not palpable. [53] Our data suggest that I-PTT can be administered at thermal doses comparable to S-PTT in murine neuroblastoma models. Further, I-PTT heats a larger area at or above the tissue thermal breakpoint.…”
Section: I-ptt Expands the Treatment Zone At Or Above The Thermal Bre...mentioning
confidence: 63%
See 1 more Smart Citation
“…Although the area at or above the thermal breakpoint of 43 °C includes tissue/skin that may not present a palpable tumor, providing this treatment at areas surrounding the tumor margin could improve the treatment's efficacy to eliminate tumor cells at the margins that are not palpable. [53] Our data suggest that I-PTT can be administered at thermal doses comparable to S-PTT in murine neuroblastoma models. Further, I-PTT heats a larger area at or above the tissue thermal breakpoint.…”
Section: I-ptt Expands the Treatment Zone At Or Above The Thermal Bre...mentioning
confidence: 63%
“…The tumor margin has been implicated as the source for tumor recurrence in many ablative therapies, particularly when the ablation/treatment zones do not extend far from the target tumor area. [53,[59][60][61] With PTT, if the thermal ablation area excludes tumor margins, tumor recurrence occurs rapidly. [62] In vivo, when I-PTT was administered to mice-bearing neuroblastoma tumors at equivalent thermal doses to S-PTT (Figures 6 and 7), we observed a significantly reduced rate of tumor recurrence as compared to S-PTT, suggesting the efficacy of I-PTT is not only eradicating tumor but also controlling their margins to reduce the incidence of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective single-arm trial adding biopsy of the AZ immediately after CLM RFA achieved 97% local progression-free survival at 30 months for CLM ablated with tumor-negative biopsy and MM > 5 mm [ 30 ]. A recent, larger study validated these findings for both RFA and microwave ablation with 93% local tumor control at 12 months for biopsy-negative AZ with MM > 5 mm [ 31 ]. For biopsy-proven tumor-negative AZs, the MM size and SUV ratio were predictive surrogate imaging biomarkers of LTP [ 21 ].…”
Section: Discussionmentioning
confidence: 76%
“…A robust independent predictor of local tumor progression (LTP) and OS after CRLM ablation is the detection of tumor cells expressing Ki-67 in ablation zone biopsy specimens, suggesting that these tumors may harbor ablation resistance mechanisms [ 149 , 150 , 151 , 152 , 153 ]. Ki-67 positive tumor cells on the electrode after radiofrequency ablation (RFA) of liver tumors is an independent predictor of OS and LTPFS [ 150 , 151 ].…”
Section: Biomarkers and Interventional Oncology For Crlmmentioning
confidence: 99%
“…Although size was thought to be an independent risk factor for LTP in tumors 3–5 cm, it is not as significant of a variable when the data are stratified by margins [ 151 ]. Subsequent prospective trials indicated that the combination of a minimal margin of >5 mm and a negative for tumor biopsy of the ablation zone center and margin offer consistent local tumor control over 97% after RFA [ 149 ] and over 93% for RFA and microwave ablation (MWA) [ 152 ]. In addition, the use of immediate fluorescent stains on ablation zone tissue can detect necrotic versus residual viable tumor intra-procedurally and can predict LTP at 12 months [ 153 ].…”
Section: Biomarkers and Interventional Oncology For Crlmmentioning
confidence: 99%